Визначення діагностичних параметрів екрануючого комплекту одягу для виконання ремонтних робіт під напругою в електроустановках 220–750 кВ - Стискал, В.М.; Кутін, В.М. (Технічна електродинаміка, 2012)
Screening properties of screening complete set of clothes for works under tension in 220–750 kV electrical installations are analysed. A mathematical model for the technical state determination of screening complete set of clothes in the process of his exploitation is built and analysed. Expressions for a current, that flows on the body of man, that is in a protective screening complete set, and the energy of electric-field, resulted on an ellipsoid, that replaces on volume the body of the man dressed in the screening complete set of clothes were obtained.